Importance of continuous strength development in young biathletes in a one-year training cycle during a multi-year training process - Sagiev, T. A.; Gibadullin, I. G.; Alzhanov, H. H.; Matyunina, M. V.; Kladov, E. V. (Journal of Physical Education and Sport, 2020)
The article presents a theoretical justification for the need to develop strength in the biathletes from the training groups during the entire one-year training cycle. The authors conducted the study aimed at determining the most effective method to plan the practice load volume during a training period for the development of strength and anaerobic strength endurance of various muscle groups. The research involved 56 first-rank biathletes aged 16- 18 years having an approximately equal proficiency level in ski-skating techniques and the functional vigor level. The biathletes under study were divided into 3 groups supervised by variouscoaches-instructors and trained according to various training programs. The 1st biathlete group was focused mainly on the lower limb strength development, the 2nd group - upper extremities, the 3rd group - comprehensive development of all muscle groups, arms, legs, and torso. At the end of the training period, the testing was performed. It showed that the indicators for cross-country and flat-country trainingare significantly higher for the 3rd group of biathletes who have medium and high levels of strength development and anaerobic strength endurance of the muscles of arms, legs and abdomen compared to the 1st and 2nd groups of athletes. The 2nd group of biathletes covered a 10-kilometer distance of the broken ground faster than the 1st group of biathletes. In the flat-country skiing conditions, the 1st group of biathletes with a strong shoulder girdle have an advantage, since they covered the distance faster compared to the 2nd group of biathletes.